Analisis Motivasi, Kepuasan Kerja dan Komitmen Terhadap Kinerja Karyawan pada PT Gergas Utama - Arif Nur Qhalis; Sri Rahayu (Economic Reviews Journal, 2024)
The research analysis aims to find out whether motivation, job satisfaction and organizational commitment influence employee performance. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 60 respondents. Primary data collection uses a questionnaire. The research results show that the t value is 2.432 > t table of 2.00 with a significant value of 0.019 < 0.05, so the hypothesis H1 is accepted and H0 is rejected, meaning that motivation has a partially positive and significant effect on employee performance at PT Gergas Utama. The t value is 3.926 > t table of 2.00 with a significant value of 0.000 < 0.05, so the hypothesis H2 is accepted and H0 is rejected, meaning that job satisfaction has a partially positive and significant effect on employee performance at PT Gergas Utama. The t value is 6.545 > t table of 2.00 with a significant value of 0.000 < 0.05, so the hypothesis H3 is accepted and H0 is rejected, meaning that organizational commitment has a partially positive and significant effect on employee performance at PT Gergas Utama. The calculated F value is 45.081 which is greater than 2.78 and the significant value of 0.000 is smaller than 0.05 so it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected so it can be concluded that motivation, job satisfaction and organizational commitment have a significant simultaneous effect on performance of PT Gergas Utama employees. The adjusted R Square value is 0.731 which can be called the coefficient of determination, which in this case means that 73.1% of employee performance can be obtained and explained by human relations, individual behavior and monkey ethos while the remaining 26.9% is explained by other factors or variables outside the research model. The adjusted R Square value is 0.691 which can be called the coefficient of determination, which in this case means that 69.1% of employee performance can be obtained and explained by motivation, job satisfaction and organizational commitment while the remaining 30.9% is explained by other factors or variables outside the research model